PHONETICS AND TECHNOLOGY: THE IMPACT OF SPEECH RECOGNITION SYSTEMS (SCIENCE TIME JOURNAL, 2025)
The integration of phonetics into technology has significantly transformed the field of speech recognition systems. This article examines the relationship between phonetics and modern speech recognition technology, highlighting the advancements made possible by understanding the acoustic and articulatory properties of speech sounds. It explores the various applications of speech recognition systems across different industries, the challenges posed by accents and dialects, and the future implications of phonetic research in improving recognition accuracy. By bridging the gap between linguistic theory and practical application, this article underscores the importance of phonetics in enhancing the efficacy of speech recognition systems.